Python for kids a playful introduction to programming - Briggs, Jason R. (San Francisco, CA No Starch Press, 2013)
Introduces the basics of the Python programming language, covering how to use data structures, organize and reuse code, draw shapes and patterns with turtle, and create games and animations with tkinter.
Includes index.
1070L
103580
Keywords: Computer software; Computer programming; Python (Computer program language); STEM - Education; Juvenile works